Impulse Breakdown of Liquids - Ushakov, Vasily Y.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2007)
The book describes the main physical processes and phenomena in pulsed electric breakdown. The knowledge and the control of the electric breakdown of liquids is important not only for the insulation inside power systems but it is also used for the creation and information of high voltage and high current pulses. Such high-voltage micro- and nanosecond pulses find wide application in experimental physics, electro discharge technology, physics of dielectrics, radar detection and ranging, high-speed photography. The nature of charge carriers, mechanism of formation and evolution of the gas phase, and their role in charge ignition (initiation) and development are considered. In particular, the spatiotemporal laws of propagation and parameters of charge channels are described in detail and the boundery conditions of the breakdown initiation are formulated. The monograph is useful for experts in high-voltage pulsed technology, physics of dielectrics, and electrical insulation as well as to students of the corresponding fields.
Behavior of Liquids in Strong Electric Fields -- Behaviour of the Gas Phase in Liquids in Strong Electric Fields -- Discharge Propagation in Short Gaps with a Quasiuniform Field -- Discharge Propagation in Gaps with a Non-Uniform Field -- Statistical Investigations of the Electrical Breakdown -- Basic Laws Describing of the Impulse Electric Strength of Liquids -- Physical Discharge Initiation (Ignition) Mechanisms -- Mechanisms of Discharge Propagation and their Applicability Limits.
Keywords: Engineering; Energy; Electric power production; Electronics; Microelectronics; Engineering; Energy Technology; Electronics and Microelectronics, Instrumentation; Energy, general; Electronic books